A linear relationship between the tensile, thermal and gas barrier properties of mape modified rubber toughened nanocomposites - Jamal, Nur Ayuni; Anuar, Hazleen; Abdul Razak, Shamsul Bahri (IIUM Press, 2010)
The nanocomposites with the application of compatibilizer agent were developed aiming to enhance the tensile, crystallization as well as gas barrier properties. Nanocomposites based on high density polyethylene (HDPE), ethylene propylene diene monomer (EPDM) and organophilic montmorillonite (OMMT) clays were prepared via melt compounding followed by compression molding. The addition of clay as well as compatibilizer agent (maleic anhydride polyethylene (MAPE)) considerably improved the tensile properties of nanocomposites systems. The largest improvement in mechanical and thermal properties occurred at clay loading levels of 4% (2-8 wt %) with MAPE system. Interestingly, the increased in tensile properties also resulted in improvement in thermal and gas barrier properties. Based on the optimum finding in tensile test, differential scanning calorimeter analysis (DSC) and gas barrier analysis were evaluated at 4 vol% of OMMT. DSC analysis revealed that the gas barrier property of nanocomposite was influenced by the crystalline percentage of nanocomposite. Along with crystalline percentage, the crystallization temperature, Tc and melting temperature, Tm were also improved with the presence of OMMT and MAPE agent. The d-spacings of the clay in nanocomposites was monitored using x-ray diffraction (XRD) and the extent of delamination was examined by transmission electron microscope (TEM). The wide angle of XRD patterns showed the increased of interplanar spacing, d of clay layers, indicating enhanced compatibility between polymer matrix and OMMT, with the aids of MAPE agent. TEM photomicrographs illustrated the mixed intercalated and partial exfoliated structures of the nanocomposites with OMMT and MAPE agent.